Parental Alienation Syndrome: A critique - Willis, Brendan; O’Donohue, William (Revista de estudios e investigación en psicología y educación, 2018)
Parental alienation syndrome (PAS), as defined by its creator Dr. Richard Gardner (2001), is a poorly defined, poorly researched, and controversial pseudoscientific construct arising primarily in the context of child custody disputes. The syndrome allegedly manifests as a non-rational and unjustified campaign of denigration against one parent during custody proceedings. It is purported to result from the combination of a parent’s “brainwashing” and indoctrination regarding the vilification of the target parent. Unfortunately, there is little evidence to support that parental alienation represents a scientifically valid syndrome. There is no commonly recognized or empirically supported pathogenies, course, familiar pattern, or treatment selection indicated for the proposed symptoms of PAS. Additionally, it has been consistently excluded from both DSM-V and ICD-10, representing a near global rejection by the scientific community. When used in the legal context, PAS is exceptionally dangerous as it can conceal actual cases of abuse and cause children to be remanded into the custody of an abusive parent. Furthermore, it can be used as leverage to separate children from the caregiver that they are best suited to be with solely on the accusation of the non-preferred parent that they have been “alienated.” In the interest of improving the scientific quality of custody evaluations and the safety of children, pseudoscientific theories such as parental alienation syndrome should be eliminated from the custody decision making process.